Das letzte Gericht Studien zur Endgerichtserwartung von den Schriftpropheten bis Jesus - Stettler, Christian (Mohr Siebeck, 2019)
Christian Stettler shows how the expectation of the last judgment developed from the classical prophets to Jesus. Deeply rooted in ancient royal ideology and world-order tradition, the various expectations of a last judgment are ultimately unified by the hope that YHWH would establish his kingdom by means of a universal judgment. While early Jewish movements and texts agree that only those who are 'just' according to the Torah will be part of this kingdom, the question of who the 'just' are and how a person becomes 'just' is answered in different ways. From here E. P. Sanders' influential 'covenantal nomism' theory is critically analyzed. - John the Baptist and Jesus are part of the apocalyptic movement. A new element in Jesus' teaching is that he expects himself and his death to play a decisive part in the last judgment.